2011
DOI: 10.3109/02713683.2011.553307
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biomechanical Properties during the Menstrual Cycle

Abstract: Corneal biomechanical properties and intraocular pressure as measured by an ocular response analyzer do not change statistically significantly during the different phases of the menstrual cycle. We conclude that measurements of the ocular response analyzer can be safely utilized in healthy female subjects without considering the possible effects of varying hormonal levels during the menstrual cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“… 13 Seymenoğlu et al determined corneal biometric properties during the menstrual cycle by using the ocular response analyzer. 14 In contrast to Goldich et al’s study, they could not find differences in corneal biomechanical properties and intraocular pressure during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 57%
“… 13 Seymenoğlu et al determined corneal biometric properties during the menstrual cycle by using the ocular response analyzer. 14 In contrast to Goldich et al’s study, they could not find differences in corneal biomechanical properties and intraocular pressure during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 57%
“…6,22-25 A recent study analyzing dry eye symptoms over the normal menstrual cycle reported worsening of ocular surface parameters related to eye dryness and inflammation during the follicular phase, especially in dry eye patients; however, subjective dry eye symptoms increased during the luteal phase, which they attributed to the ‘premenstrual syndrome’ (PMS). 23 Central corneal thickness appears to increase around ovulation and the end of the menstrual cycle, both of which occur after estrogen peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the effects of normal cycling oestrogen on IOP have been inconclusive. Although an early study suggested that IOP is highest in the menstrual phase (when oestrogen is lowest; Salvati 1923), more recent studies have shown no change across the menstrual cycle (Qureshi et al 1997, Seymenoglu et al 2011. Oestrogen has also been implicated in AMD in older females, where contraceptive use and postmenopausal HRT lower the risk of developing it.…”
Section: Eye Disease and The Retinamentioning
confidence: 99%